ADVANCED LARYNGEAL CANCER (LITERATURE REVIEW) - Z. A-G. Radzhabova; M. A. Kotov; M. A. Ebert; A. S. Mitrophanov; M. A. Radzhabova; E. V. Levchenko (Сибирский онкологический журнал, 2019)
Background. Squamous carcinoma of the larynx is still the most common head and neck cancer in many Western countries. The larynx plays a key role for many essential functions, including breathing, voice production, airway protection, and swallowing. According to the world literature, 23,800 new cases of laryngeal cancer and 106,000 deaths from this disease are registered annually in the world. Laryngeal cancer treatment is aimed at achieving tumor control while optimizing functional outcomes.Objective: to review available data on surgical and non-surgical treatment options for locally advanced laryngeal cancer, as well as the evidence supporting each of these, including oncological outcomes (overall survival, disease-free survival, local control of the disease, functional outcomes and quality of life).Material and Methods. A systematic literature search was conducted in the electronic databases Medline, Cochrane Library, and Elibrary in the interval time between 1987 and 2016.Conclusions. In recent decades, the treatment paradigm for advanced laryngeal cancer has shifted from surgery (total laryngectomy) as the gold standard of treatment to nonsurgical organ-preserving treatment using radiation therapy or chemoradiation therapy. However, concerns have arisen regarding functional outcomes after chemoradiation therapy, as well as a possible reduction in overall survival in laryngeal cancer patients, risk factors, laryngectomy.